De la academia al monumento. Las hazañas del duque de Alburquerque y el Espejo poético (1662) - Samuel Fasquel (Criticón, 2013)
In 1662 several poets gathered in order to celebrate the return in Spain of the duke of Alburquerque, who had been viceroy of México from 1653 to 1660. After this literary assembly a book was published which presented together the verses created on such occasion. This article studies the poetics of this collection of poems analizing its paratexts, the disposition of the individual works and the elements that give an internal coherence to the book.